Solomon sneezes a-choo - Singer, Marilyn; Floca, Brian (London Harper collins, 1999)
Perfect for the young slapstick fan, this zany story shows the hilarious consequences of a sneeze that shakes the world
For ages 3 and up
3
Keywords: Sneezing -- Juvenile fiction; Picture books for children -- 1999